Physical Activity in the Prevention and Management of Type 2 Diabetes Evidence-Based Approaches - Czarnota, Maksymilian; Wojdat-Krupa, Karolina; Wasyluk, Martyna; Rogowska, Monika; Ossowska, Weronika; Lewaśkiewicz, Paulina; Sikora, Karol; Płudowska, Klaudia; Przelaskowska, Aleksandra; Puliński, Jan (Quality in Sport, 2025)
Type 2 diabetes mellitus (T2DM) is a growing global health concern linked to sedentary lifestyles and obesity. Physical activity is a key factor in prevention and management, yet existing guidelines may not fully address the needs of physically active individuals. This narrative review synthesizes data from randomized controlled trials, systematic reviews, meta-analyses, and expert guidelines from the past 15 years. It focuses on the metabolic effects of exercise and practical recommendations tailored to various activity levels. Structured physical activity improves insulin sensitivity, lowers HbA1c, supports weight control, and reduces cardiovascular risk. Combined aerobic and resistance training yields the most consistent benefits. In active individuals, monitoring glucose levels, preventing hypoglycemia, and adjusting training volume are essential. Digital tools and interdisciplinary care can enhance adherence and safety. Physical activity is a cornerstone of T2DM care. Individualized exercise strategies aligned with fitness level and treatment needs can optimize outcomes. Future studies should focus on highly active populations and technology-based interventions to support personalized, sustainable exercise programs.